Dinosaur ichnofauna of the Upper Jurassic/Lower Cretaceous of the Paraná Basin (Brazil and Uruguay). (November 2015) - Francischini, H.; Dentzien–Dias, P.C.; Fernandes, M.A.; Schultz, C.L.
Abstract: Upper Jurassic and Lower Cretaceous sedimentary layers are represented in the Brazilian Paraná Basin by the fluvio–aeolian Guará Formation and the Botucatu Formation palaeoerg, respectively, overlapped by the volcanic Serra Geral Formation. In Uruguay, the corresponding sedimentary units are named Batoví and Rivera Members (both from the Tacuarembó Formation), and the lava flows constitute the Arapey Formation (also in Paraná Basin). Despite the lack of body fossils in the mentioned Brazilian formations, Guará/Batoví dinosaur fauna is composed of theropod, ornithopod and wide–gauge sauropod tracks and isolated footprints, as well as theropod teeth. In turn, the Botucatu/Rivera dinosaur fauna is represented by theropod and ornithopod ichnofossils smaller than those from the underlying units. The analysis of these dinosaur ichnological records and comparisons with other global Mesozoic ichnofauna indicates that there is a size reduction in dinosaur fauna in the more arid Botucatu/Rivera environment, which is dominated by aeolian dunes. The absence of sauropod trackways in the Botucatu Sandstone fits with the increasingly arid conditions because it is difficult for heavy animals to walk on sandy dunes, as well as to obtain the required amount of food resources. This comparison between the Upper Jurassic and Lower Cretaceous dinosaur fauna in south Brazil and Uruguay demonstrates the influence of aridization on the size of animals occupying each habitat. Graphical abstract: Highlights: Guará/Batoví (fluvio-aeolian) and Botucatu/Rivera (aeolian) units are compared. Theropod and ornithopod traces are present in both units. Botucatu paleoerg lacks sauropod traces. Dinosaur ichnofauna of Guará/Batoví is larger than Botucatu ones. Aridity of Botucatu paleoerg limits the dinosaur fauna in size and distribution.